The Shema in John's Gospel - Baron, Lori A. 1959-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
Cover -- Title -- Acknowledgements -- Table of Contents -- Chapter 1: Introduction -- Chapter 2: The Shema in Deuteronomy -- 2.1 Introduction -- 2.2 Moses's First Speech (Deut 1-4:43) -- 2.3 Hearing or obedience -- 2.4 The Uniqueness of YHWH -- 2.5 Love -- 2.6 Life -- 2.7 Moses's Second Speech (Deut 4:44-28:68) -- 2.8 The Four Themes in the Decalogue (Deut 5:1-21) -- 2.9 The Shema: Deut 6:4-9 in its Biblical Context -- 2.10 Deut 13: Warning against Hearing the False Prophet -- 2.11 Deuteronomy 26-28: Blessings and Curses -- 2.12 Moses's Third Speech (Deut 29-30) -- 2.13 Summary and Conclusions -- Chapter 3: The Shema in the Hebrew Bible beyond Deuteronomy -- 3.1 Introduction -- 3.2 Methodology -- 3.3 Joshua -- 3.4 1 and 2 Kings/2 Chronicles -- 3.5 Nehemiah -- 3.6 Psalms -- 3.7 Proverbs -- 3.8 Jeremiah -- 3.9 Zechariah -- 3.10 Malachi -- 3.11 Summary and Conclusions -- Chapter 4: The Shema in Second Temple Literature -- 4.1 Introduction -- 4.2 The Shema in Second Temple Literature (Other Than the Dead Sea Scrolls, Philo, and Josephus) -- 4.3 The Shema in the Dead Sea Scrolls (DSS) -- 4.4 The Shema in Philo -- 4.5 The Shema in Josephus -- 4.6 The Shema in Second Temple Judaism: Conclusions -- Chapter 5: The Shema in the New Testament -- 5.1 Introduction -- 5.2 The Shema According to Mark -- 5.3 The Shema According to Matthew -- 5.4 The Shema according to Luke -- 5.5 The Shema in Pauline Literature -- 5.6 Hebrews -- 5.7 James -- 5.8 Summary and Conclusions: The Shema in the New Testament -- Chapter 6: The Shema in the Gospel of John -- 6.1 Introduction -- 6.2 History of Research -- 6.3 The Shema and its themes in John 5, 8, and 10 -- Chapter 7: The Shema and its themes in the Farewell Discourse -- 7.1 Introduction -- 7.2 The Shema in John 14-15 -- 7.3 The Shema in John 17 -- 7.4 John 13: The Shema and the New Commandment.
"The Shema (Deut 6:4-5) is the lens through which Lori A. Baron explores Johannine Christology and the fraught relationship between John's Gospel and Judaism. She begins by examining the use of the Shema in the Hebrew Bible and Second Temple literature, where it is frequently evoked in scenes of covenant renewal; to support adherence to Jewish law; and in prophetic oracles of restoration. The Shema functions similarly in John's Gospel, where Jesus' unity with God is expressed in terms of the 'oneness' of the Shema (e.g., 10:30; 17:21-23): Jesus is within the divine unity. While the Synoptic Gospels cite the Shema explicitly and while Paul uses the Shema christologically, in John, the Shema is an apologetic foil against accusations of bitheism; it is used polemically against Jesus' opponents; and it signals that followers of Jesus represent the promised restoration of Israel."-- Provided by publisher
Description based on publisher supplied metadata and other sources
Keywords: Bible -- Criticism, interpretation, etc; Shema; Bible -- Relation to Deuteronomy; Bible -- Relation to the Old Testament; Bible -- Relation to John; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Electronic books; Hochschulschrift